Fully joint inversion of the 2016 Mw 7.6 Chiloé earthquake. Issue 3 (20th October 2022) - Bravo, F; Peyrat, S; Delgado, F; Fuentes, M; Derode, B; Perez, A; Campos, J
SUMMARY: A large ( M w 7.6) megathrust earthquake occurred on 2016 December 25 in Southern Chile, south of the Chiloé Island (74.2°W, 43.3°S) in the South America–Nazca subduction zone. This earthquake was the first large event in this seismotectonic segment since the M w 9.5 1960 Valdivia megathrust earthquake and broke a 50-km-long segment of the southern part of its rupture zone. Source parameters are inferred from teleseismic broad-bands, strong motions, GPS, cGPS, InSAR and tide gauge data. We show that the joint inversion significantly improves the resolution of the slip distribution, taking advantage of each data set. Our slip models predict a single slip patch of 70 km × 60 km with a maximum slip of 3.2 ± 0.8 m and a moment magnitude of 7.64. The hypothesis from previous studies that the Chiloé earthquake released energy accumulated before the Valdivia earthquake is not supported by the ensemble of geodetic, seismological and tsunami data. Hence, the Chiloé earthquake most likely released all the strain accumulated in the rupture area since the 1960 earthquake.